Electrochemically Catalyzed N–N Coupling and Ring Cleavage Reaction of 1H-Pyrazoles - Zandi, Sara; Sharafi-Kolkeshvandi, Mahnaz; Nikpour, Farzad (Synthesis, 2021)
The electrocatalyzed N–N coupling and ring cleavage reaction of 3-methyl-, 3,5-dimethyl-, 3-methyl-5-phenyl- and 3,5-diphenyl-1H-pyrazole was investigated and led to the electro-organic synthesis of new heterocyclic compounds. The results revealed that electrochemically produced 1H-pyrazoleox plays the role of acceptor in a reaction with the starting molecule via a N–N coupling and ring cleavage reaction of pyrazoles. The proposed reaction sequence consists of anodic oxidation, dimerization, rearrangement and reduction. The electrochemically catalyzed reactions were accomplished under constant-current and constant-potential conditions using an undivided electrochemical cell with the advantages of mild reaction conditions, remarkable yields and environmental compatibility.
Keywords: electrocatalysis; electrosynthesis; cyclic voltammetry; N–N coupling reaction; pyrazole ring cleavage